THE EFFECT OF IMPULSIVE BEHAVIOR AND PANIC BUYING K-POP MERCHANDISE PURCHASE INTEREST IN GROUP ORDERS THROUGH FAN LOYALTY - Sophie Adifa (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
The Korean Wave, also known as Hallyu, is a wave of Korean culture that has reached its peak of popularity and spread to various countries worldwide, including Indonesia. The cultures that have entered include music, food, and clothing. Currently, many young people in Indonesia follow the fashion trends from South Korea. This is due to the development of music culture from South Korea, which has now entered Indonesia several years ago. One that has attracted quite a lot of attention is music from South Korea, or what we usually know as K-pop. K-pop merchandise is a variety of knick-knacks related to K-pop idols, usually in the form of albums, lightsticks, stickers, bags, necklaces, keyrings, or standing figures (Lisa, 2018). According to the majority of K-pop fans, purchasing merchandise is not only based on considerations of the usefulness of the item; they consider that merchandise has symbolic benefits, such as recognition from their fan group. The more merchandise is purchased, the more it is seen that he is a fan who supports his idol (Amalia, 2019). This can show the loyal attitude of K-pop fans towards their idols, so it can be said that they buy merchandise only to get satisfaction, not based on need. Another cause of consumer behavior is panic buying because many agencies provide differences between the first printing of an album and subsequent printings. Loyalty is also a strong element in determining a company's achievements (Suhaily & Soelasih, 2018). K-Pop fans tend to have a high level of loyalty, which is evidenced by the high sales of everything related to the artists they idolize, for example, concert tickets, merchandise, and several local brands that collaborate with K-Pop idols.